1970
DOI: 10.2334/josnusd1959.12.112
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Study of Tomes' Fibers

Abstract: Dental hard tissues have been studied by the use of the scanning electron microscope, but Tomes' fibers which occupy the dentinal tubules have not yet been observed in detail. In the present study, the scanning electron microscope shows Tomes' fibers very clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Dentinal tubules observed at the fractured surface of the dentin were practically empty and the tubule wall consisted of peritubular dentin. In a few dentinal tubules, cytoplasmic processes of odontoblasts similar to those observed by KUWAJIMA et al (6) were noted.…”
Section: Resultssupporting
confidence: 82%
“…Dentinal tubules observed at the fractured surface of the dentin were practically empty and the tubule wall consisted of peritubular dentin. In a few dentinal tubules, cytoplasmic processes of odontoblasts similar to those observed by KUWAJIMA et al (6) were noted.…”
Section: Resultssupporting
confidence: 82%
“…This probably represents an artifact developed in the process of preparation of the specimen [3]. Although KUWAJIMA et al [1] showed smooth Tomes' fibers, the rough appearance of the surface of Tomes' fibers is clearly seen in this observation (Fig. 2).…”
mentioning
confidence: 70%
“…Numerous studies using scanning electron microscopy (SEM) (Boyde and Lester, 1967;Kubota et al, 1969;Kuwajima et al, 1970;Brannstrom and Garberoglio, 1972;Garberoglio and Brannstrom, 1976;Tidmarsh, 1981;Thomas And Carella, 1983) and transmission electron microscopy (TEM) (Garant, 1972;Holland 1975Holland , 1976Thomas, 1979;Frank and Voegel, 1980;Thomas, 1983;Thomas and Payne, 1983) have suggested that the odontoblast processes are limited to the inner/pulpal third of the dentin. In more recent SEM studies, process-like structures have been documented extending up to the dentino-enamel junction (DEJ) (Kelley et al, 1981;Crooks et al, 1983;Grossman and Austin, 1983;Maniatopoulos and Smith, 1983;Gunji and Kobayashi, 1983;Yamada et al, 1983;Shroff et al, 1984;Szabo et al, 1984; for discussion of these points, see Sigal et al, 1984 a,b).…”
Section: Introductionmentioning
confidence: 99%